Isolation And Partial Purification Of Protein And Detection Of Antimicrobial Activity In Leaf Extracts Of Tephrosia Cinerea (L) Pers.- An Ethno-Medicinal Plant Practiced By Tribal Community At Biligirirangana Hills Of Karnataka, India. - PANDURANGA MURTHY,G.,,; MOKSHITH, M.C,; RAVISHANKAR, H.G, (International Journal of Pharma and Bio Sciences, 2011)
Aqueous and Organic solvent extracts of Tephrosia cinerea, (L) Pers. an ethno-medicinal plant practiced by Tribal (Soliga) community against wound healing at Biligirirangana Hills of Karnataka have been evaluated for its bioactivity. The leaves were used to isolate and purify Proteins and ammonium sulphate fractionation yield 2.4 gm/ml. A single prominent peak was obtained on sephadex G-75 column with fraction 6th showing maximum bioactivity. TLC of ethyl acetate, acetone and petroleum ether extracts yielded three spots with Rf value of 0.85. The native Page revealed that, the presence of four bands and their positions suggested that, the protein present appears to be medium to low molecular size. However, the molecular characterization of the purified protein was very much essential to ascertain the nature of the same. Antimicrobial activity of organic solvent extracts, such as Acetone, Ethyl acetate and Petroleum ether were tested against pathogenic bacteria i.e., Gram +ve (E.coli) and Gram –ve (Pseudomonas aeruginosa) which were isolated from infected patients of the authorized hospital. The result reveals that, both Acetone (7.2mm) and Ethyl acetate (6.3mm) showed significant zone of inhibition against P. aeruginosa. But, Petroleum ether did not show any positive activity against P. aeruginosa. Similarly, both Ethyl acetate and Petroleum ether did not show activity against E. coli, whereas, Acetone extract of T. cinerea inhibited the growth of E.coli (9mm) and are significantly superior over other solvent extracts. Besides, the total content of phenolics in the sample was found to be 212.5 mg/ml. Hence, the obtained result suggests, susceptibility of both bacterial strains to the organic as well as purified extracts of tested ethno-medicinal plant. In addition, this plant would also exert several beneficial effects by virtue of its antibacterial activity and could be harnessed as drug formulation based on the tribal practice. The further investigation however is required to ascertain these in vitro results which are attainable in vivo through biophysical characterization of isolated bioactive constituents after complete purification.